Can financial payments incentivize short-term smoking cessation in orthopaedic trauma patients? Evidence from a discrete choice experiment - Dana Alkhoury; Jared Atchison; Antonio J. Trujillo; Kimberly Oslin; Katherine P. Frey; Robert V. O'Toole; Renan C. Castillo; Nathan N. O'Hara (Health Economics Review, 2021)
Background: Smoking increases the risk of complications and related costs after an orthopaedic fracture. Research in other populations suggests that a one-time payment may incentivize smoking cessation. However, little is known on fracture patients' willingness to accept financial incentives to stop smoking; and the level of incentive required to motivate smoking cessation in this population. This study aimed to estimate the financial threshold required to motivate fracture patients to stop smoking after injury. Methods: This cross-sectional study utilized a discrete choice experiment (DCE) to elicit patient preferences towards financial incentives and reduced complications associated with smoking cessation. We presented participants with 12 hypothetical options with several attributes with varying levels. The respondents' data was used to determine the utility of each attribute level and the relative importance associated with each attribute. Results: Of the 130 enrolled patients, 79% reported an interest in quitting smoking. We estimated the financial incentive to be of greater relative importance (ri) (45%) than any of the included clinical benefits of smoking cessations (deep infection (ri: 24%), bone healing complications (ri: 19%), and superficial infections (ri: 12%)). A one-time payment of 800 provided the greatest utility to the respondents (0.64, 95% CI: 0.36 to 0.93), surpassing the utility associated with a single 1000 financial incentive (0.36, 95% CI: 0.18 to 0.55). Conclusions: Financial incentives may be an effective tool to promote smoking cessation in the orthopaedic trauma population. The findings of this study define optimal payment thresholds for smoking cessation programs.
Keywords: 330